2014
DOI: 10.1002/qj.2430
|View full text |Cite
|
Sign up to set email alerts
|

The assimilation of horizontal line‐of‐sight wind information into the ECMWF data assimilation and forecasting system. Part I: The assessment of wind impact

Abstract: In preparation for the Aeolus Doppler Wind Lidar satellite mission, single‐component wind information from conventional observations was assimilated into the ECMWF data assimilation system. Various Observing System Experiments have been designed and performed in order to estimate the impact of such information in numerical weather prediction. The evaluation used various adjoint diagnostic tools and traditional statistical verification methods. The importance of assimilating wind observations as either single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 37 publications
6
74
0
Order By: Relevance
“…The improvements in intensity with radiance data (temperature and moisture) are evident due to improvements in the model thermodynamics. Earlier studies (Kalnay et al, 1985;Cress and Wergen, 2001;Horanyi et al, 2014) have reported the importance of wind observations compared to mass observations in the tropics in assimilation and forecast systems. The present results show higher impacts of motion vectors relative to radiances in TC predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in intensity with radiance data (temperature and moisture) are evident due to improvements in the model thermodynamics. Earlier studies (Kalnay et al, 1985;Cress and Wergen, 2001;Horanyi et al, 2014) have reported the importance of wind observations compared to mass observations in the tropics in assimilation and forecast systems. The present results show higher impacts of motion vectors relative to radiances in TC predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing need of monitoring the atmospheric boundary layer for a broad range of technological and scientific pursuits -such as for meteorology (Banta et al, 2002;Calhoun et al, 2006;Emeis et al, 2007;Horanyi et al, 2015;Vanderwende et al, 2015;Bonin et al, 2015), renewable energy (Thresher et al, 2008;Jones and Bouamane, 2011;Aitken et al, 2014;Iungo, 2016) and air traffic management (George and Yang, 2012;Smalikho and Banakh, 2015) -has led to a rapid development of remotesensing measurement techniques, such as wind lidars Cariou, 2015;Simley and Pao, 2012;Iungo andPorté-Agel, 2013, 2014) and radars (Farnet and Stevens, 1990;O'Hora and Bech, 2007;Hirth and Schroeder, 2013;Hirth et al, 2015). Compared to classical meteorological towers, remote-sensing instruments allow easier deployment, enhanced capability of varying deployment locations and potentially lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that line-of-sight winds have 70% of the value of full vector winds (Horányi et al 2015a) and that "sensitive" areas where observations are needed to improve forecasts are often cloudy (McNally 2002). Preparatory mission studies confirm that any artifacts associated with the polarization diversity technique should be rare and can easily be identified and rejected.…”
Section: Challenge and Summarymentioning
confidence: 97%
“…The winds from WIVERN are only line of sight but Horányi et al (2015a) have demonstrated that, with a state-of-the-art data assimilation system and real observations, HLOS winds such as would be obtained from an aircraft provide about 70% of the impact of a vector wind, and that in the tropics the impacts of wind data are much greater than the mass information. McNally (2002) provides further evidence for the potential impact of in-cloud winds.…”
Section: The Impact Of Wind Observations On Global Nwp Modelsmentioning
confidence: 99%
See 1 more Smart Citation